Ocena żywotności drzew oraz biomasy i morfologii systemów korzeniowych sosny zwyczajnej (Pinus sylvestris L.) wzrastającej na zrekultywowanym składowisku odpadów po flotacji rud cynku i ołowiu - Pietrzykowski, Marcin; Likus-Cieślik, Justyna; Pająk, Marek; Woś, Bartłomiej (Leśne Prace Badawcze, 2017)
The stability of introduced stands depends not only on aboveground but also on the belowground biomass. Results from reclaimed sites often indicate good growth of the aboveground part of stands, but data on the development of root systems are still lacking. Our aim was to assess the vitality of trees, their biomass and the morphology of the root systems of Scots pine ( Pinus sylvestris L.) introduced on reclaimed landfill waste after zinc and lead flotation in Bukowno (southern Poland). The landfill site was reclaimed 20 years ago and reclamation treatments involved isolation and covering with mineral substrate layers (110–150 cm thickness) which formed a technogenic soil profile. Four research plots (10×10m) were set up in pure pine stands where soil profiles consisted entirely of flotation waste. Trees on the plots were assayed according to the Kraft and IUFRO classification system. In total, 15 trees of average growth parameters and bio-sociological position (I and II Kraft class) were selected for biomass and root system analyses and the root systems were excavated, washed, measured, weighed and photographed. Our results support pine as a useful species in reforestation of post-mining areas. However, although pine trees were characterized by good vitality, their root systems were shallow and their depth reduced by up to 60 cm due to strong skeletal loamy substrate. Individual root biomass ranged from 1.2 to 9.1 kg and was comparable to pine root biomass on other reclaimed mining sites. This indicates that during restoration, the thickness of the substrate covering the flotation waste should be increased or the amount of skeletal substrate in the top layers of technosol reduced.